THE EFFECT OF TILAPIA FISH SKIN COLLAGEN ADDITION LEVEL ON THE PHYSICAL-CHEMICAL QUALITY OF BODY CREAM - Pramesti, Adriana Putri; Junianto, Junianto; Herawati, Heti; Rostini, Iis (Jurnal Perikanan Unram, 2025)
An alternate raw material for the production of collagen is the skin of tilapia fish, which is a fishery waste. As a naturally occurring humectant that helps to keep skin moisture, collagen is frequently found in cosmetic goods like body cream. The goal of this study is to ascertain the ideal amount of tilapia skin collagen to add in order to produce body cream with the best physico-chemical quality. This work employed an experimental approach using a complete randomized design (CRD) that included five replications and four treatments of increasing the collagen concentration of tilapia skin: 0%, 3%, 3.5%, and 4%. Cream pH, cream homogeneity, cream spreadability, and cream wetness were among the parameters measured. While the cream's pH, spreadability, and moisture were statistically parametrically assessed using analysis of variance (ANOVA), the homogeneity of the cream was analyzed descriptively and compared. The study's findings indicated that 4% was the ideal amount of tilapia skin collagen to add to the cream. Cream containing 4% collagen from tilapia fish skin has uniform properties, a pH of 6.08, a spreadability of 5.88 cm, and the greatest moisture percentage of 68.7%.